1999
DOI: 10.1007/s002449900532
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PCB Congeners, DDE, Hexachlorobenzene, and Methylsulfonyl Metabolites of PCB and DDE Among Various Fractions of Human Blood Plasma

Abstract: The concentrations of chlorinated biphenyls (CBs), 1, 1-bis(4-chlorophenyl)-2,2-dichloroethene (DDE), hexachlorobenzene (HCB), and the methylsulfonyl metabolites of CBs (MeSO(2)-CBs) and DDE (MeSO(2)-DDE) were determined in human plasma samples and in the fractions obtained by ultracentrifugation of plasma into very-low-density (VLDL), low-density (LDL), high-density (HDL) lipoprotein and lipoprotein depleted (LPDP) fractions (containing primarily albumin). The concentrations of triacylglycerols, cholesterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 35 publications
3
44
0
1
Order By: Relevance
“…The concentrations were about three times higher in LDL/VLDL compared to HDL, consistent with previous results (Norén et al 1999). In line with plasma analyses (Faerch et al 2012;Lind et al 2012), the non-dioxin-like congeners PCB#138, PCB#153, PCB#170 and PCB#180 were found in the highest concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The concentrations were about three times higher in LDL/VLDL compared to HDL, consistent with previous results (Norén et al 1999). In line with plasma analyses (Faerch et al 2012;Lind et al 2012), the non-dioxin-like congeners PCB#138, PCB#153, PCB#170 and PCB#180 were found in the highest concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…However, beside a previous study showing that a large fraction of POPs are associated to LDL/VLDL and HDL in healthy individuals (Norén et al 1999), little is known about the human lipoprotein distribution of POPs in vivo and how this relates to disease progress. The aims of the current study were 1) to assess the distribution of POPs in lipoprotein fractions and 2) to investigate if the distributions differ in healthy controls as compared to subjects with CVD or cancer and 3) to investigate whether the POP levels can influence the activity of HDL-associated PON1.…”
Section: Introductionmentioning
confidence: 98%
“…liver, lung, adrenal cortex and uterus). Norén and co-workers examined MeSO 2 -PCBs and 3-MeSO 2 -DDE in various fractions of human plasma and found that these metabolites were, to a higher extent than the parent PCB and DDE compounds, associated with the protein rich fraction of the blood rather than with the lipoproteins (Norén et al, 1999). Comparing maternal with the corresponding paired cord samples, concentrations of MeSO 2 -PCB were about 1.5 times higher in the mothers than in their cord blood on a lipid weight basis (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Methylsulfonyl metabolites of PCBs and DDE have also been analysed in human blood, milk, adipose tissue, lung, liver and brain (Haraguchi et al, 1986b;Norén et al, 1999;Chu et al, 2003;Hovander et al, 2006). The MeSO 2 -PCBs and MeSO 2 -DDE are highly lipophilic leading to their accumulation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Although accounting for lipid levels is sensible, roughly half of serum PCBs are associated with albumin and other proteins that are not lipoproteins (36,37). Whether albumin levels vary substantially among pregnant women from different populations is not clear, although it seems likely that variations in lipid concentration would be a greater source of variation in PCBs.…”
Section: Discussionmentioning
confidence: 99%